Different Cabergoline Effect on Metabolic and Anthropometric Parameters in Female Prolactinoma Patients Versus Idiopathic Hyperprolactinemia Patients - Aboelnaga, Mohamed M.; Eladawy, Eman H.; Elshafei, Maha M.; Abdullah, Nahed; Shaer, Moustafa El. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Hyperprolactinemia can lead to weight gain, insulin resistance, abnormal glucose homeostasis and dyslipidemia. Reversibility of these changes after normalization of prolactin with dopamine agonists is still controversial and needs more clarification. Objective: We aimed to: 1) evaluate and compare metabolic and anthropometric profile in female with newly diagnosed prolactin-secreting adenoma versus female idiopathic hyperprolactinemic patients; 2) compare the effects of one year cabergoline therapy on the metabolic profile and anthropometric parameters (by using visceral adiposity index as index for evaluation of adipose tissue dysfunction) in females with prolactinoma to female idiopathic hyperprolactinemic patients. Patients and Methods: We enrolled 40 female patients with newly diagnosed prolactinoma and 40 female patients with idiopathic hyperprolactinemia, who were matched according to: age; weight; BMI; waist; and prolactin levels. We enrolled the participants in this study at the time of diagnosis before therapy and they were followed up for 12 months. Results: Cabergoline therapy had significant favorable effects on metabolic and anthropometric parameters, visceral adiposity index and in all patients (apart from HDLc in prolactinoma patients). Cabergoline therapy was significantly more effective in patient with idiopathic hyperprolactinemia than prolactinoma patients with regard to BMI, waist circumference, HDLc and visceral adiposity index despite normalization of prolactin levels in both groups. Conclusion: 12 months of Cabergoline treatment improved most of the anthropometric and metabolic parameters, and visceral adiposity index as a marker for adipose tissue dysfunction in both idiopathic hyperprolactinemia and prolactinoma patients. However, Cabergoline treatment was more effective in idiopathic hyperprolactinemic than prolactinoma patients.
Keywords: VAI